Is there a Future for Regional Banks and Regional Exchanges? The Strategies of Selected Austrian Finance Institutions - David T. Llewellyn; Reinhard Ortner; Helmut Stepic; Stefan K. Zapotocky (SUERF - The European Money and Finance Forum, 2002)
1) D.T. Llewellyn, " The future for small & regional banks in Europe" 2) R. Ortner, " What future for regional banks?" 3) H. Stepic, " The Strategy of RZB in Central and Eastern Europe" 4) St. K. Zapotocky, " The challenges and chances of regional exchanges" It has been argued that the combination of technological advance, the European Single Market, the advent of EMU and, more generally, the reality of a global financial community, is undermining the competitive position of small, regional financial organisations, be they banks, stock exchanges or other financial entities. This line of argument leads to the conclusion that there is no viable business future for the small. This SUERF Study offers points of view to the contrary, both from the academic and " practitioners" angle. Professor David Llewellyn contributes the academic view, strongly arguing that size per se is not the issue but rather that efficient, well focused small and medium-sized financial institutions remain viable. Representatives of three regional financial institutions in Austria were asked to discuss elements of their business strategy to substantiate their belief in the viability of their institution's future. The contribution by Reinhard Ortner (Erste Bank) is based on a talk he gave on the occasion of the 22nd SUERF Colloquium in Vienna in 2000, and that of Helmut Stepic (Raiffeisen Zentralbank) on a speech at the Alpbacher Banking Seminar in 2001. The consolidation and concentration process has, of course, also engulfed stock exchanges and many of the small ones have already been pronounced terminally ill. Stefan Zapotocky (Wiener Börse AG) is firm in his view that regional exchanges will have a viable future catering for regional financing needs. His contribution is based on a presentation at the SUERF Salzburg Seminar of 2002, which dealt with the future of regional exchanges.
Keywords: F3; G2; 330; small banks; bank strategy; regional banks; banking in Central Europe; Bank; Bankgeschäft; Börse; Region; Internationaler Wettbewerb; Strategisches Management; Europa